HUBUNGAN TENAGA KERJA DAN KETERBUKAAN EKONOMI UNTUK PERTUMBUHAN EKONOMI INDONESIA - Sa'diatun Ni'mah; Fitrah Sari Islami (LP2M Universitas Bina Bangsa, 2023)
The purpose of this study is to analyze the impact of labor and economic opening on Indonesia's economic growth in the short and long term. This study uses secondary data obtained from the World Bank during the period 1990-2020. With independent variables including Labor (TK), Exports, Imports and the dependent variable is Economic Growth (PE). Then to achieve the target of this research, it includes several time series econometric strategies such as Dickey Fuller-Generalized Least Square (DF-GLS), Engle Granger-Augmented Dickey Fuller cointegration test (EG-ADF), and Error-Correction Model (ECM). The results of the ECM test show that there is a long-term and temporary relationship between the factors used and economic development. Surprisingly in this study, in the long term, labor has a negative impact on economic development in Indonesia. In addition to labor, the export variable, both in the short and long term, also has a negative impact on economic development